MANAJEMEN POTENSI OBJEK WISATA ALAM TAMAN NASIONAL BOGANI NANI WARTABONE DI DESA TORAUT KECAMATAN DUMOGA BARAT KABUPATEN BOLAANG MONGONDOW - NURHAMIDIN, DJAMILA; RORONG, ARIE JUNUS; MAMBO, RULLY (Sam Ratulangi University, 2020)
The management and development of the tourism sector is one of the efforts to improve theeconomy, social and environment of a country. Various potentials of tourism objects that are developed arenatural tourism potentials which are mostly owned by developing countries including Indonesia, it can bedeveloped as an economic activity that can generate foreign exchange quickly. Potential is something thatcan be made as a material or a source that will be managed either through human effort or throughmechanical power where the potential can also be interpreted as resources that are around us. A touristattraction is anything that exists in a tourist destination that is an attraction for people to want to come visitthe place. In this study using a type of qualitative research in which this research is descriptive in naturethat is conducting in-depth interviews gathering primary data and collecting secondary data, which thenresults of primary and secondary data are processed and data will be obtained. The results showed that theplanning of the management of the natural tourism potential of TNBW in the village of Toraut had longbeen planned but was constrained by funding problems because the budget for TNBW itself was only forthe preservation and restoration of natural ecosystems, whereas from the local government in this case theBolaang Mongongow Tourism Office had no budget assistance funds for that so that planning is hampered,planning for managing tourism potential in TNBW reappears after the formation of the KPA Tarsius, inthe initial stages, KPA Tarsius has submitted proposals to the TNBW after being approved by the KPAdirectly conducting surveys and presenting the results of the location survey that will be made touristattractions, after that the TNBW met with EPASS as the grant funders assisted by the TNBW. Theorganizing done by TNBW both to the ranks of TNBW and to the KPA tarsier is very well arranged so thatthe stalled plans resulting in funding problems can be overcome. Finally, the supervision conducted byTNBW and KPA tarsiers around the TNBW site continues to run until now, by conducting routine patrolsin the TNBW area and locations that have attractive tourism potential for the community, so they cancontinue to be preserved.Keywords: Management, Potential, Tourist Attraction.